Heuristic assessment : professional judgement and final report cards in Ontario secondary schools - Cavanaugh, Gordon (2016)
This thesis explored teacher professional judgement as applied to the final report card process of Ontario Secondary School courses in Business, Humanities, and Social Science. A constructivist grounded theory approach was used. Twenty-four active teachers from various schools participated in semi-structured interviews and follow-up questions. How the respondents understood the use of professional judgement when determining percentage grades was analyzed. The study found that the participants personalized procedures, either independently or at the direction of the local administration, when interpreting policy into practice. These practices, although done with good intentions, were at odds with reliable and valid assessment. This phenomenon was termed Heuristic Assessment. Ontario’s revised assessment and evaluation policy Growing Success (Ontario, 2010a) placed emphasis on informed professional judgement. Although a definition was provided, how the concept works in practice was open to interpretation. Therefore, schools can apply professional judgement in numerous ways and still be in line with provincial policy if what is taught and evaluated correspond with curriculum documents. However, this study found that Ministry instructions are challenging to implement. There are tensions between how the local administration view policy, participant understanding of these guidelines, and the realities of the classroom. Furthermore, school culture consists of both shared, or public, and shadowed, or private practices. Shared and shadowed practices sometimes go with, and sometimes against, provincial policy. Consequently, participants engaged in Heuristic Assessment: they used their professional judgement to adhere to local policy in appearance, while finding ways to evaluate final report cards on their own terms. This study makes several contributions to the field of knowledge. First, we see the concept of professional judgement in Ontario evaluation practices not as an idealized definition but as teacher-created construct. Second, there was clear evidence that the province still has work to do in order to have better consistency in assessment of learning practices. Understanding gained by the research established proposals on how to further improve reporting of student learning in Ontario and other educational systems. For example, there are easier ways for teachers to explain the meaning of grades to students, parents, guardians, and other stakeholders. If professional judgement is vital to evaluation practices, then the concept should be reified to assist teachers with the assessment process. There is also a methodological contribution, as the study provided an example of how to blend the constructivist grounded theory of Kathy Charmaz with the situational analysis of Adele Clarke to educational evaluation research.